ChemInform Abstract: Copper‐Catalyzed One‐Pot Denitrogenative‐Dehydrogenative‐Decarboxylative Coupling of β‐Ketoacids with Trifluorodiazoethane: Facile Access to Trifluoromethylated Aldol Products. Issue 3 (January 2015) - Xiong, Heng‐Ying; Yang, Zhen‐Yan; Chen, Zhen; Zeng, Jun‐Liang; Nie, Jing; Ma, Jun‐An
Abstract The novel copper‐catalyzed cross‐coupling of β‐ketoacids with in situ generated trifluorodiazoethane proceeds under mild conditions to give trifluoromethylated aldol products.